2015
DOI: 10.1080/02640414.2015.1061199
|View full text |Cite
|
Sign up to set email alerts
|

Influence of moderate intensity physical activity levels and gender on conditioned pain modulation

Abstract: This study examined the potential influence of moderate intensity physical activity (PA) levels and gender on central pain modulation using conditioned pain modulation (CPM) in healthy men and women. Twenty four individuals (12 men and 12 women) who reported engaging in the moderate intensity PA for 150 min or more per week and 24 individuals (12 men and 12 women) who reported engaging in moderate intensity PA for 60 min or less per week completed a self-report PA questionnaire and a 7-day PA assessment using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Although the underlying mechanisms of the PA effect on chronic pain are still poorly understood, growing evidence from experimental studies demonstrates that physically active individuals, such as endurance athletes, typically show reduced sensitivity to experimental pain stimuli compared to normally active healthy individuals [32,33,34]. Furthermore, there is some evidence that those who are sufficiently physically active to meet the PA recommendations show reduced sensitivity to experimental pain stimuli [35] and greater CPM when compared to those who are not sufficiently active [36]. Additionally, results from exercise intervention studies show that individuals who have completed an aerobic exercise intervention exhibit decreased sensitivity to experimental pain stimuli compared to before the intervention [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Although the underlying mechanisms of the PA effect on chronic pain are still poorly understood, growing evidence from experimental studies demonstrates that physically active individuals, such as endurance athletes, typically show reduced sensitivity to experimental pain stimuli compared to normally active healthy individuals [32,33,34]. Furthermore, there is some evidence that those who are sufficiently physically active to meet the PA recommendations show reduced sensitivity to experimental pain stimuli [35] and greater CPM when compared to those who are not sufficiently active [36]. Additionally, results from exercise intervention studies show that individuals who have completed an aerobic exercise intervention exhibit decreased sensitivity to experimental pain stimuli compared to before the intervention [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Flood et al (2017) also reported greater CPM among endurance athletes than controls, although Tesarz et al (2013) could not demonstrate such an effect. CPM also correlated with the frequency of training among non-athletes (Umeda, Lee, Marino, & Hilliard, 2016). Although these studies cannot determine whether improved pain modulation related to endurance sport is inherited or acquired, longitudinal studies in animal models show that aerobic exercise for several weeks can reduce pain-like behaviour (Bobinski et al, 2015;Tian et al, 2018) supporting the latter possibility.…”
Section: The Effects Of the Type Of Sport On Pain Perception And Momentioning
confidence: 97%
“…The well-described phenomenon of exercise-induced hypoalgesia (EIH) (Naugle et al, 2012) suggests that exercise can reduce pain directly via adjustments at some point(s) in the transduction, transmission and processing of noxious stimuli. Though typically investigated for acute bouts of exercise, there is evidence from cross-sectional (Ellingson et al, 2012; Naugle and Riley, 2014; Lemming et al, 2015; Umeda et al, 2016a) and longitudinal (Anshel and Russell, 1994; Jones et al, 2014) studies that long-term exercise can lead to sustained hypoalgesic effects in healthy adults. EIH is usually measured by obtaining a threshold, tolerance and/or rating of a noxious stimulus and is greatest when mechanical stimuli are used to evoke pain (Koltyn, 2000; Naugle et al, 2012).…”
Section: Introductionmentioning
confidence: 99%